Myalgias and facial edema - Wakim, Gerard (2017)
BACKGROUND: Henoch-Schönlein purpura (HSP), the most common childhood vasculitis, is classically associated with the appearance of non-thrombocytopenic purpura. Nevertheless, unspecific systemic symptoms such as abdominal pain and arthralgias may precede the hallmark trait. A rare manifestation of HSP, typically seen in children less than 2 years of age, is facial edema. CASE REPORT: We report the case of an 8-year-old girl who presented initially with myalgias, and only later developing purpura and facial edema indicative of an underlying vasculitis. CONCLUSIONS: Failure to identify atypical presentations of HSP may lead to delays in treatment, prolong hospital stay, and end-organ damage. This case highlights the rare but possible signs and symptoms of HSP with an emphasis on the heterogeneity of the disease.